2012
DOI: 10.1016/j.ijid.2012.02.006
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of Japanese encephalitis in South Korea, 2007–2010

Abstract: Although JE has traditionally been regarded as a children's disease, the majority of cases now occur in adults in countries where strong immunization programs exist, such as in South Korea. Consideration should be given to an adult vaccination policy in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 15 publications
0
62
0
Order By: Relevance
“…The odds ratio (OR) for cohort 1976–1980 compared to 1981–1986 (the reference) was 0.56; that is, the cohort 1976–1980 has approximately half odds of being positive than those of the cohort 1981–1986.The waning immunity phenomenon was less clear for the 1970–1975 and 1963–1969 cohorts, who received two or three doses (over 20 years since the last booster dose), because the positive rates were 54% for both cohorts. By contrast, among the people who were not vaccinated, the high seropositive rate of JE-neutralizing antibodies in the cohort born before 1952 was likely caused by a high frequency of early natural infection, as well as accumulated exposure, which induces a stronger immunological memory response than does vaccination [17], [18], [20], [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The odds ratio (OR) for cohort 1976–1980 compared to 1981–1986 (the reference) was 0.56; that is, the cohort 1976–1980 has approximately half odds of being positive than those of the cohort 1981–1986.The waning immunity phenomenon was less clear for the 1970–1975 and 1963–1969 cohorts, who received two or three doses (over 20 years since the last booster dose), because the positive rates were 54% for both cohorts. By contrast, among the people who were not vaccinated, the high seropositive rate of JE-neutralizing antibodies in the cohort born before 1952 was likely caused by a high frequency of early natural infection, as well as accumulated exposure, which induces a stronger immunological memory response than does vaccination [17], [18], [20], [32].…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of the JE vaccination policy across Taiwan, JE cases shifted from children to adults [13], and this pattern has also been observed in neighboring countries such as Japan and South Korea [11], [17], [18]. Several studies on the seroprevalence of JE were conducted in Taiwan in the 1990s; however, these studies were confined to small local areas, and their definition of seropositivity of antibodies was inconsistent [19][21].…”
Section: Introductionmentioning
confidence: 99%
“…The improved vaccine was introduced into the routine immunization program in Japan in 1967, when > 1000 cases per year occurred, and the number of reported cases has since decreased markedly, with < 10 cases reported annually since 1992 [78]. Similar trends have been observed in China [79], Korea [80,81], Malaysia [82], Nepal [83], Sri Lanka [84], Taiwan [85], Thailand [86,87] and Vietnam [88]. These observations clearly indicate that JE is a vaccinepreventable infectious disease.…”
Section: Vaccinesmentioning
confidence: 84%
“…17 In Korea, 86.7% of the confirmed cases were in adults older than 40 years. 18 However, we performed a more detailed analysis here on the incidence rates of JE in the four regions of Taiwan and found that incidence rates were variable in the different regions ( Figure 2C), which resulted in providing us more information about the risk of JE infections.…”
Section: Discussionmentioning
confidence: 99%